Impaction fractures of the anterior tibial plafond: Outcomes after fractures around the ankle: Is the anterior impaction plafond fracture a problem?. Issue 2 (21st June 2020) - Chohan, Moaz B.Y.; Del Balso, Christopher; Ching, Michael; Schemitsch, Emil; Lawendy, Abdel Rahman; Sanders, David W.
Abstract: Objectives: To determine whether patients with AO/OTA 43-B anterior impaction tibial plafond fractures have worse clinical outcomes, and an increased risk of progression to ankle arthrodesis. Design: Retrospective cohort study. Setting: Level 1 academic trauma center. Patients: One hundred sixty-eight patients were included in the study, all of whom had tibial plafond fractures. Intervention: Study patients underwent external fixation and/or open reduction internal fixation (ORIF) as indicated by fracture/injury pattern. Main outcome measurements: Arthrodesis rate. Results: AO 43-B Anterior impaction tibial plafond fractures have an increased risk of progression to arthrodesis when compared to AO 43-B nonanterior impaction type fractures (19.4% vs 8%). Conclusions: AO 43-B anterior impaction tibial plafond fractures have a worse clinical outcome compared to AO 43-B nonanterior impaction fractures. These fractures also confer increased risk of progression to arthrodesis. Conflicts of interest: The authors have no conflict of interests to declare.